Organização do conhecimento em bibliotecas digitais de Teses e Dissertações: análise da aplicabilidade das teorias macroestruturais para categorização de áreas de assunto - Bastos, Flávia Maria [UNESP] (2005)
Organizing the knowledge acquired in digital libraries is a global movement, which entails storing, preserving, providing access and disseminating scientific production. Considering the growing amount of electronic documents to organize, we propose to investigate and lay down the principles for a proper thematic structuring of the theses and dissertations in digital libraries. Our purpose is to provide help tools to elaborate those thematic structures within the field of Information Science and identify the theoretical and methodological aspects of the theories on thematic classification that can be applied when organizing the contents of theses and dissertations of the digital libraries of higher education institutions. Regarding the organization of knowledge in literature, two theoretical trends were systematized: the micro - and the macro - structural theory. The theoretical and methodological aspects of the macrostructural theory are more appropriate to reach goals, as they enable the gathering of theories from disciplines down to more general themes to explain how concepts are structured. The microstructural theory, on the contrary, concerns the theoretical corpus as the minimal unit of knowledge, and thus enables a study of the relationship between concepts. The theoretical trends within the macrostructural theory currently study the use of conceptual mapping, thematic domains, semantic fields, and terminological theories. The evaluation of those theories revealed how important the social and cultural contexts pointed out in interviews done with researchers of Instituto de Física Teórica da Universidade Estadual Paulista / UNESP, in the construction of conceptual relations of knowledge organization to be applied in digital environments moved by interactions, both in is individual use and in the multiple actors envolved - like digital libraries are.